Design of a randomised controlled trial of adapted physical activity during adjuvant treatment for localised breast cancer: the PASAPAS feasibility study. Issue 10 (28th October 2013) - Touillaud, M; Foucaut, A-M; Berthouze, S E; Reynes, E; Kempf-Lépine, A-S; Carretier, J; Pérol, D; Guillemaut, S; Chabaud, S; Bourne-Branchu, V; Perrier, L; Trédan, O; et al.
Abstract : Introduction: After a diagnosis of localised breast cancer, overweight, obesity and weight gain are negatively associated with prognosis. In contrast, maintaining an optimal weight through a balanced diet combined with regular physical activity appears to be effective protective behaviour against comorbidity or mortality after a breast cancer diagnosis. The primary aim of the Programme pour une Alimentation Saine et une Activité Physique Adaptée pour les patientes atteintes d'un cancer du Sein (PASAPAS) randomised controlled trial is to evaluate the feasibility of implementing an intervention of adapted physical activity (APA) for 6 months concomitant with the prescription of a first line of adjuvant chemotherapy. Secondary aims include assessing the acceptability of the intervention, compliance to the programme, process implementation, patients' satisfaction, evolution of biological parameters and the medicoeconomic impact of the intervention. Methods and analysis: The study population consists of 60 women eligible for adjuvant chemotherapy after a diagnosis of localised invasive breast cancer. They will be recruited during a 2-year inclusion period and randomly allocated between an APA intervention arm and a control arm following a 2:1 ratio. All participants should benefit from personalised dietetic counselling and patients allocated to the intervention arm will be offered an APA programme of two to three weekly sessions of Nordic walking and aerobic fitness. During the 6-month intervention and 6-month follow-up, four assessments will be performed including blood draw, anthropometrics and body composition measurements, and questionnaires about physical activity level, diet, lifestyle factors, psychological criteria, satisfaction with the intervention and medical data. Ethics and dissemination: The study was approved by the French Ethics Committee (Comité de Protection des Personnes Sud-Est IV) and the national agencies for biomedical studies and for privacy. All participants will give written informed consent. The study findings will be disseminated through the scientific public and serve as a foundation for future randomised controlled trials of efficacy.